2014
DOI: 10.1111/aji.12216
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1 Receptor Blockade Prevents Fetal Cortical Brain Injury but Not Preterm Birth in a Mouse Model of Inflammation‐Induced Preterm Birth and Perinatal Brain Injury

Abstract: Problem Exposure to intrauterine inflammation, associated with preterm birth, has been linked to a devastating spectrum of neurobehavioral disorders. Mechanisms of this injury are unknown. Using a mouse model of intrauterine inflammation, we have observed a disruption of fetal neuronal morphology along with a marked elevation of Interleukin (IL)-1β in the fetal brain and placenta. In the current study, we hypothesized that IL-1 plays a key role in perinatal brain injury. Method of Study Utilizing a mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 27 publications
(43 reference statements)
7
74
1
Order By: Relevance
“…Overall, our findings on the role of IL-1 concur with those previously reported by authors of this paper (17,77). Small biased ligands offer therapeutic advantages, which cannot be mimicked by currently available orthosteric inhibitors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, our findings on the role of IL-1 concur with those previously reported by authors of this paper (17,77). Small biased ligands offer therapeutic advantages, which cannot be mimicked by currently available orthosteric inhibitors.…”
Section: Discussionsupporting
confidence: 92%
“…The abdominal muscle layer was sutured, and the skin was closed with clips. A total of 100 mL 101.10 (1 mg/Kg/12 h), Kineret (4 mg/Kg/12 h), SR-11302 (1 mg/Kg/12 h), Y27632 (0.5 mg/Kg/12 h), or vehicle was injected s.c. in the neck 30 min before stimulation with IL-1b, LPS, or LTA (to allow distribution of drugs to target tissues, in line with a first efficacy preclinical study); all doses used were based on reported efficacy (17,24,25,28,29). Mice delivery was assessed every hour until term (G19-G19.5).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Since IL-1β has the potential to be damaging, its regulation is tightly controlled. Indeed, IL-1β is an important mediator of preterm birth 102,103,104,105 , and perinatal brain injury, 106,107,108,109 and can trigger the production of other pro-inflammatory cytokines and chemokines through the IL-1 receptor in a similar manner to TLRs. 55 Indeed delivery of a synthetic peptide to pregnant mice that is a selective IL-1 receptor modulator, delays IL-1β delays and LPS-induced preterm birth.…”
Section: Review Of Placental Development and Function In The Contementioning
confidence: 99%
“…Indeed, a TLR4 antagonist prevented LPS-induced preterm uterine contractility in non-human primates 100 and knockout mice for TLR or associated adapter proteins are resistant to microbial and PAMP-induced preterm birth. 83,101 Similarly, since IL-1β is a mediator of preterm birth 102,103,104,105 and fetal brain injury 106,107,108,109 studies have focused on using IL-1 receptor antagonists or selective IL-1 receptor modulators to prevent these adverse outcomes. 110,111 Thus, preventing the upstream induction of IL-1β by inhibiting placental inflammasome activity may also serve as a potential target for preventing adverse pregnancy outcomes.…”
Section: Review Of Placental Development and Function In The Contementioning
confidence: 99%